Desirable Characteristics of Accountants in the View of Rayong Industry - Petcharat, Sarita (Journal of Industrial Business Administration, 2019)
The objective of this study was to study desirable characteristics of accountants needed in Rayong Industry. The sample of 302 senior accountants was chosen for this study. Data collection employed a questionnaire which was statistically analyzed using percentage and means. The results found that desirable characteristics of accountants wee professional knowledge, skill, attitude, and experience on high level while professional ethics on extreme level based on the requirements of Rayong.